An Integration Method of UML Diagrams and Arduino UNO for Developing Water Pollution Detection System - Abdulameer Abdulmonim, Dhafer; Zainab Hassan Muhamad (The Indonesian Journal of Computer Science, 2024)
Despite the scientific and health development in the world, water pollution can pose a threat to human health, whether the pollutants are biological or chemical. In addition, traditional methods of water pollution detecting require high costs, and take time. Due to the importance of water for human life, drinking, irrigation, or for use in industry etc. Thus, reliable methods for water contamination detecting are a crucial issue.This paper aims to propose an integration method of UML diagrams and Arduino UNO microcontroller for developing water pollution detection system. The proposed method consists of three phases, which are system’s design, system's schematic and system’s architecture. It uses use case diagram and sequence diagram. In addition, the system design consisting of a microcontroller and multiple connected sensors for water pollutant detection, namely pH, turbidity, dissolved solids, temperature, oxidation reduction potential and electrical conductivity. The result of this paper is the production an automatic water pollutant detection prototype using Arduino and UML diagrams to display the water pollution parameters. The variables pH, turbidity, dissolved solids, temperature, oxidation reduction potential and electrical conductivity were chosen because they are the physical and chemical parameters that most influence water quality. The proposed system is characterized by measuring the water quality in real time, low cost and its data is accurate and fast.